Life in the Freezer : A Natural History of the Antarctic - Fothergill, Alastair; Foreword by Attenborough, David; Photographs by Osborne, Ben (London BBC Books, 1993)
Illustrated account of the wildlife of the Antarctic continent and ocean.
Include Color Illustrations, Glossary, Resources and Index.
A Natural History of the Antarctic.
Keywords: Natural history -- Antarctica -- Ecology